Benign Prostate Hyperplasia (BPH) – Induced Syndrome of Inappropriate Antidiuretic Hormone Secretion (SIADH): A Rare Precipitant of Acute Decompensated Heart Failure - Wahyu Aditya; Bunga Dewanggi; Paskariatne Probo Dewi; Teuku Muhammad Haykal Putra; Hawani Sasmaya Prameswari (Jurnal Kardiologi Indonesia, 2026)
In Acute decompensation of heart failure (ADHF), the precipitating factors need to be identified and treated promptly. Urinary retention is rarely recognized as a cause of ADHF. Here, we presented a case of Benign Prostate Hypertrophy (BPH) with urinary retention inducing SIADH, which precipitated an episode of decompensated heart failure. The correction of hyponatremia and placement of a DC catheter, along with diuretic and tolvaptan administration, dramatically improved the patient’s condition.